PLAQUE CONTROL IN PERIODONTAL DISEASE: KONTROL PLAK PADA PENYAKIT PERIODONTAL - Ni Luh Putu Sri Maryuni Adnyasari; Dwis Syahriel; I Gusti Ayu Dewi Haryani (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Periodontal disease results from a complex interplay between the subgingival biofilm and the host immune-immflamatory events that develop in the gingival and periodontal in response to the challenge presented by the bacteria. Gingivitis precedes periodontitis. In gingivitis , the inflammatory lesion is confined to the gingiva, however, with periodontits, the inflammatory processes extend to additionally affect the periodontal ligament and the alveolar bone. Review: The primary cause of gingival inflammattion is bacterial plaque. Other predisposing factors include calculus, faulty restoration complication associated with orthodontic therapy. Microbial plaque biofilm control is an effective way of treating and preventing gingivitis and is an essential part of all procedures involved in the treatment and prevention of periodontal diseases. Good supragingival biofilm control has also been shown to affect the growth and composition of subgingival plaque biofilm so that it favors a healthier microflora and reduces calculus formation. Carefully performed daily home plaque biofilm control, combined with frequent professionally delivered plaque biofilm and calculus removal, reduces the amount of supragingival biofilm, decreases the total number of microorganisms in moderately deep pockets, including furcation areas, and greatly reduces the quantity of periodontal pathogens. Chemical inhibitors of plaque biofilm and calculus that are incoporated in mouthwashes or dentifrices also play an important role in controlling microbial biofilms. Conclusion: Daily plaque biofilm control permits patients to assume responsibility for their own oral health every day.